Determination of heavy metals in surface sediments in water bodies of the chaneel dike in populations of Gambote and Soplaviento (Bolivar) - Espitia, Nevis (2014)
Heavy metals are often found in sedimentary deposits as water pollutants. For this reason in this study was carried out the determination of heavy metals (Hg, Cd, Pb, Cr, Ni, Fe) in surface sediments in Water Bodies Canal del Dique, (artificial arm cupcake River) by smooth digestion method, using the methodology of Chester and Voutsinou, finding normal levels of these metals in these water bodies, despite having contributions of the Magdalena River, and to be influenced by mining areas. A slightly higher level of nickel was found in the Cienaga Grande de Lorica (site control, no anthropogenic sources of heavy metal pollution) relative to the other sampling points because it is a site rich in nickel, but their values are in permissible values, otherwise it is a good place to use as a control for the other metals, lead was not detected by the use of this methodology.